Cortical Transformation of Wide-Field (Multiwhisker) Sensory Responses - Hirata, Akio (American Physiological Society, 2008)
In the barrel cortex of rodents, cells respond to a principal whisker (PW) and more weakly to several adjacent whiskers (AWs). Here we show that compared with PW responses, simultaneous wide-field stimulation of the PW and several AWs enhances short-latency responses and suppresses long-latency responses. Multiwhisker enhancement and suppression is first seen at the level of the cortex in layer 4 and not in the ventroposterior medial thalamus. Within the cortex, enhancement is manifested as a reduction in spike latency in layer 4 but also as an increase in spike probability in layer 2/3. Intracellular recordings revealed that multiwhisker enhancement of short-latency responses is caused by synaptic summation that can be explained by synaptic cooperativity (i.e., convergence of synaptic inputs activated by different whiskers). Conversely, multiwhisker suppression of long-latency responses is due to increased recruitment of inhibition in cortical cells. Interestingly, the ability to differentiate multiwhisker and PW responses is lost during rapid sensory adaptation caused by high-frequency whisker stimulation. The results reveal that simultaneous and temporally dispersed wide-field sensory inputs are discriminated at the level of single cells in barrel cortex with high temporal resolution, but the ability to compute this difference is highly dynamic and dependent on the level of adaptation in the thalamocortical network.